Antioxidant profiling in bael (Aegle marmelos Correa.) genotypes - Kholia, A; Misra, K K; Rai, R; Singh, N (Journal of Horticultural Sciences, 2025)
The present investigation was undertaken to characterize the non-enzymatic and enzymatic antioxidant activities among 18 bael genotypes. Amongst the bael genotypes, highest marmelosin was observed in ‘Pant Bael-1’, at par with ‘Pant Bael-15’ and ‘Pant Bael-14’. The maximum enzymatic antioxidant activity of SOD and CAT was obtained in ‘Pant Shivani’, while, maximum POD enzyme activity was recorded in ‘Pant Bael-1’. The maximum DPPH radical scavenging activity was observed from ‘Pant Shivani’. The correlation study showedpositive correlation of non-enzymatic antioxidant content and enzymatic antioxidant activity with DPPH free radical scavenging activity (%). Principal component analysis revealed that out of nine principal components axis, four had eigen values greater than one and all together account for 77.22 of the total variability.
Keywords: Antioxidants; bael; marmelosin